PENGARUH TINGKAT PENDIDIKAN, LINGKUNGAN KERJA DAN MASA KERJA TERHADAP KINERJA GURU DI LINGKUNGAN KEMENAG KABUPATEN KARANGANYAR DENGAN GENDER SEBAGAI VARIABEL MODERATOR - Panuntun, Sita (STIE AUB Surakarta)
The development of science and technology demands the availability of reliable Human Resources (HR), putting teachers as the driving force as well as the creators of the human resources. The purpose of this research is to examine the influence of education level, work environment and working period on teacher performance with gender as moderator variable.Data used is primary data by taking samples totaling 196 teachers in the Ministry of Religion, Karanganyar. The data analysis method was tested by validity test, reliability test, Stuctural Equation Modeling through Lisrel 8.70 program.The results of the study are as follows the level of education has a significant influence and positive on performance of teachers, gender can not strengthen the influence of education level on teacher performance, work environment has significant influence and positive on teacher performance. Gender can not strengthen the influence of work environment on teacher performance. Working hours has significant influence and positive on teacher performance, gender can not strengthen the effect of working hours on teacher performance. The most dominant influence on the performance of teachers is the work environment variable.Keywords: Education Level, Work Environment, Work Age, Gender, Performance